Legal Pluralism and “Tanah Ulayat”: Transforming Indigenous Land Relations and Social Re-Arrangements in Tanimbar Catholic Communities - Masriat, Cayetanus (Archīum Ateneo, 2021)
How indigenous communities compromise and adapt to land laws that shape its land tenure system is the subject of this thesis. Understanding this land tenure system, however, first requires consideration of the multiple identities that the land possesses. This study looks into these multiple identities, how they emerge and interrelate with one another, in the context of the Tanimbar community, in the regency of Maluku, Indonesia. It investigates the interplay of indigenous laws on land with those of colonial law, state law, the forces of modernity, and of particular interest, the influence of the Catholic Church in reconstructing Tanah Ulayat or customary law. Legal pluralism serves as an approach to analyze the interaction of these multiple forces. Using the ethnographic method, with in-depth interviews, focus group discussions, direct observation, reflexivity, and other methodologies such as photography, the study finds that the Tanimbar’s encounter with various legal perspectives, as well as with modern notions of progress, have indeed shaped a complicated land tenure system. Traditional notions of communal ownership, for example, confronted colonial land laws that defined different territorial boundaries on Tanimbar lands. The Tanah Ulayat also clashed with state laws that saw the land as state-owned when it serves the national interest. Modernity brought new notions of a better life, encouraging many families to sell their land for, among others, the education of children. The notion of customary land, already turning plural and complex, became even more so with the influence of the Catholic Church. v The Church and the Tanimbar have developed very close ties over decades, ties that have led the community to donate tracts of customary land for the Church to carry out its mission. In return, the Church defends the rights of the community against outside claims on their land, and campaigns against the selling of land to outside parties. These acts, however, place the Church in an ambiguous position, acting both to defend customary land and to “take” it by accepting gifts of lands. The ambiguous position further confounds the notion of customary land. It behooves future researchers to investigate developments in this reconfiguration of the land tenure system, and to seek ways to help the community unravel the knots that bind the Tanah Ulayat in Tanimbar.